Criminal Justice Drug Abuse Treatment Studies (CJ-DATS): Targeted Intervention Components (TIC) for Correctional Re-Entry Programs, 2002-2008 (United States) - Knight, Kevin ([Verlag nicht ermittelbar], 2010)
Targeted Intervention Components (TIC) for Correctional Re-Entry Programs is three-year study with the established guidelines and resources for an evidence-based library of targeted treatment intervention components for outpatient (e.g., crimes of moderate severity) re-entry correctional programs. It involves no-fee, user-friendly, and manual-guided techniques that can be integrated with programmatic assessments of client needs and progress. The TIC study, under Texas Christian University's (TCU) leadership, involved developing and testing a series of brief (4-session), flexible, evidence-based treatment interventions targeting specific offender problems. These interventions employed a user-friendly modular format that does not require extensive staff training, and the modules themselves are intended to serve either as stand-alone interventions or as components of a comprehensive treatment program. The initial modules are currently being developed and tested in prison-based treatment settings. A series of field trials test and validate each of these specialized therapeutic modules for use with community-based correctional populations. The TCU developed a treatment model which provided conceptual and scientific foundations for the use of targeted interventions that addressed discretely client problems. Study questionnaires assessed client responses that were related to such topics as: treatment readiness and motivation, anger and hostility, criminal thinking, risky behaviors for HIV/AIDS/Hepatitis C, communication, and other social skill deficits. The TCU's Criminal Justice Client Evaluation of Self and Treatment (CJ-CEST) was implemented as the core "needs and engagement" assessment instrument.